KIF11 as a Potential Marker of Spermatogenesis Within Mouse Seminiferous Tubule Cross-sections. (November 2019) - Hara-Yokoyama, Miki; Kurihara, Hidetake; Ichinose, Shozo; Matsuda, Hironori; Ichinose, Shizuko; Kurosawa, Masaru; Tada, Norihiro; Iwahara, Chihiro; Terasawa, Kazue; Podyma-Inoue, Katarzyna A.; Furukawa, Koichi; Iwabuchi, Kazuhisa
The arrangement of immature germ cells changes regularly and periodically along the axis of the seminiferous tubule, and is used to describe the progression of spermatogenesis. This description is based primarily on the changes in the acrosome and the nuclear morphology of haploid spermatids. However, such criteria cannot be applied under pathological conditions with arrested spermatid differentiation. In such settings, the changes associated with the differentiation of premeiotic germ cells must be analyzed. Here, we found that the unique bipolar motor protein, KIF11 (kinesin-5/Eg5), which functions in spindle formation during mitosis and meiosis in oocytes and early embryos, is expressed in premeiotic germ cells (spermatogonia and spermatocytes). Thus, we aimed to investigate whether KIF11 could be used to describe the progression of incomplete spermatogenesis. Interestingly, KIF11 expression was barely observed in haploid spermatids and Sertoli cells. The KIF11 staining allowed us to evaluate the progression of meiotic processes, by providing the time axis of spindle formation in both normal and spermatogenesis-arrested mutant mice. Accordingly, KIF11 has the potential to serve as an excellent marker to describe spermatogenesis, even in the absence of spermatid development.